An investigation of Confucius Institute's effects on China's OFDI via cultural difference and institutional quality. Issue 3 (29th January 2020) - Xu, Chensheng; Yao, Feng; Zhang, Fan; Wang, Yonghong
Abstract : Purpose: This study aims to investigate the influence of the Confucius Institute (CI) on outward foreign direct investment (OFDI) by China and its potential interaction with cultural difference and institutional quality in host countries. Design/methodology/approach: In the empirical study, the gravity model is adopted as the benchmark to investigate the effects of CI on China's OFDI using the ordinary least squares or Poisson Pseudo Maximum Likelihood estimators. Panel data on China's OFDI from 2004 to 2015 are used. Cultural difference and institutional quality are included explicitly as control variables to examine the effects of CI on China's OFDI. Findings: CI has a significant positive effect on China's OFDI, and this effect depends on the cultural difference and institutional quality of the host country. The impact of CI on China's OFDI is more prominent in host countries with a smaller cultural difference or lower institutional quality. Originality/value: CI is a comprehensive platform for foreign cultural exchange and signifies the rebirth of Confucianism in China. The present study shows that CI can stimulate the growth of China's OFDI, with implications for other Asian countries influenced by Confucianism. Based on the results of the study, strategies for "Going Global" and encouraging economic growth based on cultural exchange and the recognition of host country heterogeneities are proposed.